A piezoelectric ceramic material with high Curie temperature and high piezoelectric coefficient and a preparation method thereof

The existing materials were solved by introducing Ca2+ and Sr2+ as composite A-position metal ions in bismuth layered piezoelectric ceramic materials and doping LiTaO3 and LaAlO3, using transition metal oxides and lanthanide rare earth oxides as sintering aids. The problem of low piezoelectric coefficient significantly improves the Curie temperature and piezoelectric properties of the material.

CN119285356BActive Publication Date: 2025-02-14HUNAN MEICHENG NEW MATERIALS TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411847080.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-14
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The existing bismuth layered structure piezoelectric ceramic materials have a low piezoelectric coefficient, which limits their wide application in high-end technology fields.

Method used

A piezoelectric ceramic material with composite A-position metal ions Ca2+ and Sr2+ is used, combined with the doping of LiTaO3 and LaAlO3, and transition metal oxides and lanthanide rare earth oxides are used as sintering aids to adjust the lattice structure and oxygen vacancies of the material.

Benefits of technology

The Curie temperature and piezoelectric coefficient of piezoelectric ceramic materials are significantly improved, and the maximum piezoelectric constant reaches 35pC/N, exceeding the performance of existing bismuth layered piezoelectric ceramics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285356B_ABST
    Figure CN119285356B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of piezoelectric ceramic materials, in particular to a piezoelectric ceramic material with high Curie temperature and high piezoelectric coefficient and a preparation method thereof, wherein the structural formula is as follows: (1‑x‑y)(Bi2O2) 2+ (A m‑1 B m O 3m+1 ) 2‑ ‑xLiTaO3‑yLaAlO3, where A is Na + , K + , Ca 2+ , Sr 2+ , Ba 2+ , Pb 2+ 、Bi 3+ ,La 3+ Any one or more of the following; B is Fe 3+ 、Ti 4+ , Nb 5+ , W 6+ Any one or more of the composites; m is an integer between 1‑4; 0<x≤0.2; 0<y≤0.2. The piezoelectric ceramic material prepared by the present invention has a high Curie temperature and excellent electrochemical properties. The maximum piezoelectric constant can reach 35pC / N, which is significantly improved compared with the currently reported bismuth layered structure piezoelectric ceramics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of piezoelectric ceramic materials, in particular to a piezoelectric ceramic material with high Curie temperature and high piezoelectric coefficient and a preparation method thereof. Background Art

[0002] Piezoelectric materials are an important type of functional materials with important applications in many fields of the national economy. In high-end technology fields such as energy, aerospace, and defense industry, the application of piezoelectric materials has shifted from conventional use to service in extreme environments, which requires piezoelectric materials and piezoelectric sensors to be able to operate at higher temperatures.

[0003] Bismuth layered piezoelectric ceramics have attracted widespread attention from researchers due to their special layered structure and high Curie temperature. However, current studies have found that the piezoelectric coefficient of prototype bismuth layered piezoelectric ceramics is generally only 5-20pC / N. The low piezoelectric coefficient limits its wide application. Summary of the invention

[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a piezoelectric ceramic material with high Curie temperature and high piezoelectric coefficient and a preparation method thereof.

[0005] The technical solutions adopted are as follows:

[0006] A piezoelectric ceramic material with high Curie temperature and high piezoelectric coefficient, the structural formula of the piezoelectric ceramic material is as follows:

[0007] (1-xy)(Bi 2 O 2 ) 2+ (A m-1 B m O 3m+1 ) 2- -xLiTaO 3 -yLaAlO 3

[0008] Among them, A is Ca 2+ and / or Sr 2+ ;

[0009] B is Nb 5+ ;

[0010] m is an integer between 1 and 4;

[0011] 0<x≤0.2;

[0012] 0<y≤0.2;

[0013] It also includes a sintering aid, which is a transition metal oxide and / or a lanthanide rare earth oxide;

[0014] The transition metal oxide is manganese oxide and / or copper oxide;

[0015] The lanthanide rare earth oxide is a composite of any one or more of cerium oxide, samarium oxide, and dysprosium oxide;

[0016] The amount of the sintering aid is (1-xy)(Bi 2 O 2 ) 2+ (A m-1 B m O 3m+1 ) 2- -xLiTaO 3 -yLaAlO 3 0.1-1% of mass.

[0017] Furthermore, m is preferably 2.

[0018] Furthermore, when the sintering aid is a combination of transition metal oxide and lanthanide rare earth oxide, the performance of the piezoelectric ceramic material is optimal;

[0019] Further, when the sintering aid is a combination of a transition metal oxide and a lanthanide rare earth oxide, the mass ratio of the transition metal oxide to the lanthanide rare earth oxide can be selected from 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, preferably 1:1;

[0020] Furthermore, the amount of the sintering aid is (1-xy)(Bi 2 O 2 ) 2+ (A m-1 B m O 3m+1 ) 2- -xLiTaO 3 -yLaAlO 3 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, preferably 0.5% of the mass.

[0021] Furthermore, the transition metal oxide is preferably copper oxide.

[0022] Furthermore, the lanthanide rare earth oxide is preferably cerium oxide.

[0023] Furthermore, A is preferably Ca 2+ and Sr 2+ , Ca 2+ and Sr 2+The molar ratio of Ca can be selected from 1:1, 1:2, 1:3, 1:4, 2:1, 3:1, 4, 2+ and Sr 2+ The molar ratio is preferably 1:4.

[0024] Further, 0.05≤x≤0.15, 0.01≤y≤0.05;

[0025] Furthermore, x=0.1, y=0.025.

[0026] The present invention also provides a method for preparing a piezoelectric ceramic material:

[0027] Bi 2 O 3 , Oxidation A, Oxidation B are mixed, ball milled once, dried and pre-sintered at 600-800℃, and then mixed with LiTaO 3 、LaAlO 3 , sintering aids, and then ball-milled for the second time, dried, granulated, pressed, and debinded. Finally, sintered at 1050-1200℃ for 1-4h.

[0028] Beneficial effects of the present invention:

[0029] The present invention provides a piezoelectric ceramic material with high Curie temperature and high piezoelectric coefficient. 2 Nb 2 O 9 The piezoelectric coefficient is greater than that of CaBi 2 Nb 2 O 9 , but the Curie temperature is far lower than that of Ca 2+ and Sr 2+ As a complex A-site metal ion, Ca 2+ Replace part of Sr 2+ The unit cell volume and ion displacement polarization are then reduced, and the electric domain is stabilized, thereby increasing the Curie temperature.

[0030] LiTaO 3 and LaAlO 3 All of them belong to perovskite structure compounds. At present, there have been reports on the introduction of perovskite structure compounds into KNN and PZT piezoelectric ceramics, but there has been no report on the introduction of LiTaO 3 or / or LaAlO 3 Bismuth layered piezoelectric ceramics reported in this application LiTaO 3 and LaAlO 3The moderate lattice distortion caused by the doping of Bi and the reduction of oxygen vacancy concentration caused by Bi volatilization weaken the pinning effect, increase the number of reversible domains, improve the polarizability and piezoelectric activity of piezoelectric ceramic materials, and achieve the effect of improving their piezoelectric properties. The introduction of sintering aids promotes moderate lattice distortion or vacancies inside the piezoelectric ceramic material, which also makes it easier for the domain wall to flip under the action of the electric field, thereby improving the polarization efficiency and further improving its piezoelectric properties. It can also reduce the sintering temperature, improve the microstructure of the ceramic, reduce the porosity and increase its density, thereby improving the piezoelectric properties.

[0031] The piezoelectric ceramic material prepared by the present invention has a relatively high Curie temperature (above 500°C) and excellent electrochemical properties. The maximum piezoelectric constant can reach 35pC / N, which is a significant improvement compared to the currently reported bismuth layered structure piezoelectric ceramics. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a SEM photograph of the polished thermally corroded surface of the piezoelectric ceramic material in Example 1. It can be seen that the internal density is relatively high and no obvious pores are observed. DETAILED DESCRIPTION

[0033] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0034] Embodiment 1:

[0035] This embodiment provides a piezoelectric ceramic material with a high Curie temperature and a high piezoelectric coefficient, including 0.875Bi in a mass ratio of 100:0.25:0.25 2 Ca 0.2 Sr 0.8 Nb 2 O 9 -0.1LiTaO 3 -0.025LaAlO 3 , CuO and CeO 2 ;

[0036] Preparation method of the above piezoelectric ceramic material:

[0037] Bi 2 O 3 、CaCO 3 、SrCO 3 , Nb 2 O 5The mixture was added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After being ball milled for 10 h on a planetary ball mill, it was dried, placed in a mold, pressed into a sheet at 10 MPa, and then heated to 750 °C at a rate of 5 °C / min for 1 h. After the pre-burning, the product was crushed and mixed with LiTaO 3 、LaAlO 3 , CuO, CeO 2 Mix and add into a ball mill, use anhydrous ethanol as the ball milling medium, perform secondary ball milling on a planetary ball mill for 10 hours and then dry, add 10wt% concentration of PVA solution as a binder to granulate, and the obtained granules are passed through a 120-mesh sieve and placed in a mold and pressed into a billet under a pressure of 100MPa. The billet is heated to 650℃ at a rate of 1℃ / min, kept warm for 1 hour to debind, and then continued to heat to 1100℃ and sintered for 2 hours.

[0038] Embodiment 2:

[0039] This embodiment provides a piezoelectric ceramic material with a high Curie temperature and a high piezoelectric coefficient, including 0.875Bi in a mass ratio of 100:0.25:0.25 2 Ca 0.2 Sr 0.8 Nb 2 O 9 -0.1LiTaO 3 -0.025LaAlO 3 , CuO and CeO 2 ;

[0040] Preparation method of the above piezoelectric ceramic material:

[0041] Bi 2 O 3 、CaCO 3 、SrCO 3 , Nb 2 O 5 The mixture was added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After being ball milled for 10 h on a planetary ball mill, it was dried, placed in a mold, pressed into a sheet at 10 MPa, and then heated to 750 °C at a rate of 5 °C / min for 1 h. After the pre-burning, the product was crushed and mixed with LiTaO 3 、LaAlO 3 , CuO, CeO 2 Mix and add into a ball mill, use anhydrous ethanol as the ball milling medium, perform secondary ball milling on a planetary ball mill for 10 hours and then dry, add 10wt% concentration of PVA solution as a binder to granulate, and the obtained granules are passed through a 120-mesh sieve and placed in a mold and pressed into a billet under a pressure of 100MPa. Heat the billet to 650℃ at a rate of 1℃ / min, keep it for 1 hour to debind, and then continue to heat to 1050℃ and keep it for sintering for 2 hours.

[0042] Embodiment 3:

[0043] This embodiment provides a piezoelectric ceramic material with a high Curie temperature and a high piezoelectric coefficient, including 0.875Bi in a mass ratio of 100:0.25:0.25 2 Ca 0.2 Sr 0.8 Nb 2 O 9 -0.1LiTaO 3 -0.025LaAlO 3 , CuO and CeO 2 ;

[0044] Preparation method of the above piezoelectric ceramic material:

[0045] Bi 2 O 3 、CaCO 3 、SrCO 3 , Nb 2 O 5 The mixture was added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After being ball milled for 10 h on a planetary ball mill, it was dried, placed in a mold, pressed into a sheet at 10 MPa, and then heated to 750 °C at a rate of 5 °C / min for 1 h. After the pre-burning, the product was crushed and mixed with LiTaO 3 、LaAlO 3 , CuO, CeO 2 Mix and add into a ball mill, use anhydrous ethanol as the ball milling medium, perform secondary ball milling on a planetary ball mill for 10 hours and then dry, add 10wt% concentration of PVA solution as a binder to granulate, and the obtained granules are passed through a 120-mesh sieve and placed in a mold and pressed into a billet under a pressure of 100MPa. Heat the billet to 650℃ at a rate of 1℃ / min, keep it for 1 hour to debind, and then continue to heat to 1150℃ and keep it for 2 hours.

[0046] Embodiment 4:

[0047] This embodiment provides a piezoelectric ceramic material with a high Curie temperature and a high piezoelectric coefficient, including 0.875Bi in a mass ratio of 100:0.25:0.25 2 Ca 0.2 Sr 0.8 Nb 2 O 9 -0.1LiTaO 3 -0.025LaAlO 3 , CuO and CeO 2 ;

[0048] Preparation method of the above piezoelectric ceramic material:

[0049] Bi 2 O 3 、CaCO 3 、SrCO 3 , Nb 2 O 5 The mixture was added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After being ball milled for 10 h on a planetary ball mill, it was dried, placed in a mold, pressed into a sheet at 10 MPa, and then heated to 750 °C at a rate of 5 °C / min for 1 h. After the pre-burning, the product was crushed and mixed with LiTaO 3 、LaAlO 3 , CuO, CeO 2 Mix and add into a ball mill, use anhydrous ethanol as the ball milling medium, perform secondary ball milling on a planetary ball mill for 10 hours and then dry, add 10wt% concentration of PVA solution as a binder to granulate, and the obtained granules are passed through a 120-mesh sieve and placed in a mold and pressed into a billet under a pressure of 100MPa. Heat the billet to 650℃ at a rate of 1℃ / min, keep it for 1 hour to debind, and then continue to heat to 1200℃ and keep it for sintering for 2 hours.

[0050] Comparative Example 1:

[0051] This comparative example provides a piezoelectric ceramic material with a high Curie temperature and a high piezoelectric coefficient, and its structural formula is 0.875Bi 2 Ca 0.2 Sr 0.8 Nb 2 O 9 -0.1LiTaO 3 -0.025LaAlO 3 ;

[0052] Preparation method of the above piezoelectric ceramic material:

[0053] Bi 2 O 3 、CaCO 3 、SrCO 3 , Nb 2 O 5 The mixture was added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After being ball milled for 10 h on a planetary ball mill, it was dried, placed in a mold, pressed into a sheet at 10 MPa, and then heated to 750 °C at a rate of 5 °C / min for 1 h. After the pre-burning, the product was crushed and mixed with LiTaO 3 、LaAlO 3Mix and add into a ball mill, use anhydrous ethanol as the ball milling medium, perform secondary ball milling on a planetary ball mill for 10 hours and then dry, add 10wt% concentration of PVA solution as a binder to granulate, and the obtained granules are passed through a 120-mesh sieve and placed in a mold and pressed into a billet under a pressure of 100MPa. The billet is heated to 650℃ at a rate of 1℃ / min, kept warm for 1 hour to debind, and then continued to heat to 1100℃ and sintered for 2 hours.

[0054] Comparative Example 2:

[0055] This comparative example provides a piezoelectric ceramic material with a high Curie temperature and a high piezoelectric coefficient, including 0.875Bi with a mass ratio of 100:0.5 2 Ca 0.2 Sr 0.8 Nb 2 O 9 -0.1LiTaO 3 -0.025LaAlO 3 and CuO;

[0056] Preparation method of the above piezoelectric ceramic material:

[0057] Bi 2 O 3 、CaCO 3 、SrCO 3 , Nb 2 O 5 The mixture was added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After being ball milled for 10 h on a planetary ball mill, it was dried, placed in a mold, pressed into a sheet at 10 MPa, and then heated to 750 °C at a rate of 5 °C / min for 1 h. After the pre-burning, the product was crushed and mixed with LiTaO 3 、LaAlO 3 , CuO, added into a ball mill, with anhydrous ethanol as the ball milling medium, secondary ball milled on a planetary ball mill for 10 hours and then dried, 10wt% concentration of PVA solution was added as a binder to granulate, the obtained granules were passed through a 120-mesh sieve and placed in a mold and pressed into a billet under a pressure of 100MPa, the billet was heated to 650℃ at a speed of 1℃ / min, kept warm for 1h to debind, and then continued to heat to 1100℃ and sintered for 2h.

[0058] Comparative Example 3:

[0059] This comparative example provides a piezoelectric ceramic material with a high Curie temperature and a high piezoelectric coefficient, including 0.875Bi with a mass ratio of 100:0.5 2 Ca 0.2 Sr 0.8 Nb 2 O 9 -0.1LiTaO3 -0.025LaAlO 3 and CeO 2 ;

[0060] Preparation method of the above piezoelectric ceramic material:

[0061] Bi 2 O 3 、CaCO 3 、SrCO 3 , Nb 2 O 5 The mixture was added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After being ball milled for 10 h on a planetary ball mill, it was dried, placed in a mold, pressed into a sheet at 10 MPa, and then heated to 750 °C at a rate of 5 °C / min for 1 h. After the pre-burning, the product was crushed and mixed with LiTaO 3 、LaAlO 3 、CeO 2 Mix and add into a ball mill, use anhydrous ethanol as the ball milling medium, perform secondary ball milling on a planetary ball mill for 10 hours and then dry, add 10wt% concentration of PVA solution as a binder to granulate, and the obtained granules are passed through a 120-mesh sieve and placed in a mold and pressed into a billet under a pressure of 100MPa. The billet is heated to 650℃ at a rate of 1℃ / min, kept warm for 1 hour to debind, and then continued to heat to 1100℃ and sintered for 2 hours.

[0062] Comparative Example 4:

[0063] It is basically the same as Example 1, except that Bi 2 CaB 2 O 9 Replace Bi 2 Ca 0.2 Sr 0.8 Nb 2 O 9 .

[0064] This comparative example provides a piezoelectric ceramic material with a high Curie temperature and a high piezoelectric coefficient, including 0.875Bi in a mass ratio of 100:0.25:0.25 2 CaB 2 O 9 -0.1LiTaO 3 -0.025LaAlO 3 , CuO and CeO 2 ;

[0065] Preparation method of the above piezoelectric ceramic material:

[0066] Bi 2 O 3 、CaCO3 , Nb 2 O 5 The mixture was added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After being ball milled for 10 h on a planetary ball mill, it was dried, placed in a mold, pressed into a sheet at 10 MPa, and then heated to 750 °C at a rate of 5 °C / min for 1 h. After the pre-burning, the product was crushed and mixed with LiTaO 3 、LaAlO 3 , CuO, CeO 2 Mix and add into a ball mill, use anhydrous ethanol as the ball milling medium, perform secondary ball milling on a planetary ball mill for 10 hours and then dry, add 10wt% concentration of PVA solution as a binder to granulate, and the obtained granules are passed through a 120-mesh sieve and placed in a mold and pressed into a billet under a pressure of 100MPa. The billet is heated to 650℃ at a rate of 1℃ / min, kept warm for 1 hour to debind, and then continued to heat to 1100℃ and sintered for 2 hours.

[0067] Comparative Example 5:

[0068] It is basically the same as Example 1, except that Bi 2 Sb 2 O 9 Replace Bi 2 Ca 0.2 Sr 0.8 Nb 2 O 9 .

[0069] This comparative example provides a piezoelectric ceramic material with a high Curie temperature and a high piezoelectric coefficient, including 0.875Bi in a mass ratio of 100:0.25:0.25 2 Sb 2 O 9 -0.1LiTaO 3 -0.025LaAlO 3 , CuO and CeO 2 ;

[0070] Preparation method of the above piezoelectric ceramic material:

[0071] Bi 2 O 3 、SrCO 3 , Nb 2 O 5 The mixture was added to a ball mill, and anhydrous ethanol was used as the ball milling medium. After being ball milled for 10 h on a planetary ball mill, it was dried, placed in a mold, pressed into a sheet at 10 MPa, and then heated to 750 °C at a rate of 5 °C / min for 1 h. After the pre-burning, the product was crushed and mixed with LiTaO 3 、LaAlO 3, CuO, CeO 2 Mix and add into a ball mill, use anhydrous ethanol as the ball milling medium, perform secondary ball milling on a planetary ball mill for 10 hours and then dry, add 10wt% concentration of PVA solution as a binder to granulate, and the obtained granules are passed through a 120-mesh sieve and placed in a mold and pressed into a billet under a pressure of 100MPa. The billet is heated to 650℃ at a rate of 1℃ / min, kept warm for 1 hour to debind, and then continued to heat to 1100℃ and sintered for 2 hours.

[0072] Comparative Example 6:

[0073] The same as Example 1, except that LiTaO is not added. 3 .

[0074] Comparative Example 7:

[0075] The same as Example 1, except that LaAlO 3 .

[0076] Performance Test:

[0077] The piezoelectric ceramic materials prepared in Examples 1-4 and Comparative Examples 1-7 of the present invention were polished and then silvered, and polarized in an electric field of 7 kV / mm for 15 min in silicone oil at 100° C. and then left for one day as test samples;

[0078] The high temperature dielectric temperature spectrum test system (GJW-I) was used to measure the change of the dielectric constant of the sample with temperature, and the Curie temperature Tc was determined. The ZJ-3A quasi-static d 33 The piezoelectric constant d of the test specimen is measured by the measuring instrument 33 The measurement frequency is 110 Hz, and the Agilent 4294A precision impedance analyzer is used to measure the electrical properties of the sample, such as the mechanical quality factor Qm and the planar electromechanical coupling coefficient kp.

[0079] The test results are shown in Table 1 below:

[0080] ;

[0081] It can be seen from Table 1 above that the piezoelectric ceramic material prepared in the present invention has a relatively high Curie temperature (above 500°C) and excellent electrochemical properties. The maximum piezoelectric constant can reach 35pC / N, which is a significant improvement compared to the currently reported bismuth layered structure piezoelectric ceramics.

[0082] By comparing the data of Examples 1-4, it can be seen that when the sintering temperature is 1100°C, the piezoelectric performance of the piezoelectric ceramic material is optimal;

[0083] By comparing the data of Example 1 with those of Comparative Examples 1-3, it can be seen that CuO and CeO 2The addition of plays a positive role in increasing the Curie temperature of piezoelectric ceramic materials and improving piezoelectric properties;

[0084] By comparing the data of Example 1 with that of Comparative Example 4, it can be seen that Sr doped Bi 2 CaB 2 O 9 Although it will cause its Curie temperature to drop, it can improve its piezoelectric properties;

[0085] By comparing the data of Example 1 with that of Comparative Example 5, it can be seen that Ca doped Bi 2 Sb 2 O 9 It plays a positive role in increasing the Curie temperature of piezoelectric ceramic materials and improving piezoelectric performance;

[0086] By comparing the data of Example 1 with those of Comparative Examples 6-7, it can be seen that LiTaO 3 and LaAlO 3 It can effectively improve the Curie temperature and piezoelectric properties of piezoelectric ceramic materials.

[0087] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A piezoelectric ceramic material with high Curie temperature and high piezoelectric coefficient, characterized in that: The structural formula of the piezoelectric ceramic material is as follows: (1-x-y)(Bi2O2) 2+ (A m-1 B m O 3m+1 ) 2- -xLiTaO3-yLaAlO3 Among them, A is Ca 2+ and Sr 2+ ; B is Nb 5+ ; m is 2; 0<x≤0.2; 0<y≤0.2; It also includes a sintering aid, which is a transition metal oxide and / or a lanthanide rare earth oxide; The transition metal oxide is manganese oxide and / or copper oxide; The lanthanide rare earth oxide is a composite of any one or more of cerium oxide, samarium oxide, and dysprosium oxide; The amount of the sintering aid is (1-xy)(Bi2O2) 2+ (A m-1 B m O 3m+1 ) 2- -0.1-1% of the mass of xLiTaO3-yLaAlO3.

2. The piezoelectric ceramic material according to claim 1, characterized in that: 0.05≤x≤0.15, 0.01≤y≤0.

05.

3. The piezoelectric ceramic material according to claim 1, characterized in that: x=0.1,y=0.

025.

4. A method for preparing a piezoelectric ceramic material as claimed in any one of claims 1 to 3, characterized in that: Mix Bi2O3, A oxide and B oxide, dry and pre-sinter at 600-800℃ after ball milling once, then mix with LiTaO3, LaAlO3 and sintering aid, dry and granulate, press and debind after secondary ball milling, and finally sinter at 1050-1200℃ for 1-4h.

Citation Information

Patent Citations

  • Ca2+ doped bismuth laminated piezoceramic material and preparation method thereof

    CN101982441A

  • Sodium niobate lithium tantalate series lead-free piezoelectric ceramic composite

    CN102557635A

Cited By

  • Low-temperature co-fired piezoelectric ceramic with high Curie temperature and high piezoelectric constant and preparation method of low-temperature co-fired piezoelectric ceramic

    CN121202556A